First cases of canine infection with Hepatozoon canis in the city of Cúcuta, Colombia - Cala Delgado, Daniel Leonardo (2018)
Two cases of canines infected with Hepatozoon canis are described in the city of Cúcuta, Colombia. The first patient of 18 months of age came to consultation with vomiting, anorexia, and progressive weight loss. In the second case, it was intended to perform preventive ovariohysterectomy, but the patient presented anemia in the pre-surgical clinical tests. For both cases, the diagnosis was by blood smear, observed at 100X. For the second case the diagnose was confirmed by PCR. The treatment established was symptomatic, using drugs such as oxytetracycline and doxycycline. This is the first report of hepatozoonosis in the city of Cúcuta.